Ideal timing to transfer from an acute care hospital to an interdisciplinary inpatient rehabilitation program following a stroke: an exploratory study - Nadeau Sylvie; Gagnon Dany; Tam Vincent (BMC, 2006)
Abstract Background Timely accessibility to organized inpatient stroke rehabilitation services may become compromised since the demand for rehabilitation services following stroke is rapidly growing with no promise of additional resources. This often leads to prolonged lengths of stays in acute care facilities for individuals surviving a stroke. It is believed that this delay spent in acute care facilities may inhibit the crucial motor recovery process taking place shortly after a stroke. It is important to document the ideal timing to initiate intensive inpatient stroke rehabilitation after the neurological event. Therefore, the objective of this study was to examine the specific influence of short, moderate and long onset-admission intervals (OAI) on rehabilitation outcomes across homogeneous subgroups of patients who were admitted to a standardized interdisciplinary inpatient stroke rehabilitation program. Methods A total of 418 patients discharged from the inpatient neurological rehabilitation program at the Montreal Rehabilitation Hospital Network after a first stroke (79% of all cases reviewed) were included in this retrospective study. After conducting a matching procedure across these patients based on the degree of disability, gender, and age, a total of 40 homogeneous triads (n = 120) were formed according to the three OAI subgroups: short (less than 20 days), moderate (between 20 and 40 days) or long (over 40 days; maximum of 70 days) OAI subgroups. The rehabilitation outcomes (admission and discharge Functional Independence Measure scores (FIM), absolute and relative FIM gain scores, rehabilitation length of stay, efficiency scores) were evaluated to test for differences between the three OAI subgroups. Results Analysis revealed that the three OAI subgroups were comparable for all rehabilitation outcomes studied. No statistical difference was found for admission (P = 0.305-0.972) and discharge (P = 0.083-0.367) FIM scores, absolute (P = 0.533-0.647) and relative (P = 0.496-0.812) FIM gain scores, rehabilitation length of stay (P = 0.096), and efficiency scores (P = 0.103-0.674). Conclusion OAI does not seem to affect significantly inpatient stroke rehabilitation outcomes of patients referred from acute care facilities where rehabilitation services are rapidly initiated after the onset of the stroke and offered throughout their stay. However, other studies considering factors such as the type and intensity of the rehabilitation are required to support those results.